Preliminary report on coal boring operations, together with report on coal boring operations, 1908 [electronic resource] - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. (St. John's Nfld. : Robinson, 1917)
At head of title: Geological Survey of Newfoundland. Electronic reproduction. Mode of access: Internet. 44